PENGARUH VARIASI TEKANAN PADA MODIFIKASI BRIKET BATUBARA TERHADAP WAKTU SULUT - Devi Komalasari; Siska Wulandari (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
Briquettes are alternative energy that can be used as substitutes of petroleum and gas. Coal briquettes generally have a slowignition time. Therefore, this study modifies coal briquettes by adding a blazingstimulant of palm frond fiber and potassium chlorate. The objectives to be achieved in this study wereto find out the effect of pressure variations modificationsof coal briquettes to the ignition time. In this study, the briquetting process was done by varying pressure of 200 Psi, 300 Psi, 400 Psi, 500 psi and 600 Psi. Coal briquette powder particle size used in this study was 80-100 mesh while the particle size of oil palm frond fibers used were 40-50 mesh. The results showed that the fastest ignition time obtained at a pressure of 200 Psi with ignition time 132 seconds. In conclusion, the pressure variations on coal briquettes modifications infunced ignition time.